Philanthropy or solidarity? Ethical dilemmas about humanitarianism in crisis‐afflicted Greece. (May 2016) - Theodossopoulos, Dimitrios
Abstract: That philanthropy perpetuates the conditions that cause inequality is an old argument shared by thinkers such as Karl Marx, Oscar Wilde and Slavoj Žižek. I recorded variations of the same argument in local conversations regarding growing humanitarian concern in austerity‐ridden Greece. Local critiques of the efficacy of humanitarianism, which I explore here ethnographically, bring to the fore two parallel possibilities engendered by the 'humanitarian face' of solidarity initiatives: first, their empowering potential (where solidarity initiatives enhance local social awareness), and second, the de‐politicisation of the crisis (a liability that stems from the effectiveness of humanitarianism in ameliorating only temporarily the superficial consequences of the crisis). These two possibilities – which I treat as simultaneous and interrelated – can help us appreciate the complexity and social embeddedness of humanitarian solidarity in times of austerity.